2009
DOI: 10.1128/mcb.00824-08
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Polysome Profiling Reveals an Inflammation-Responsive Posttranscriptional Operon in Gamma Interferon-Activated Monocytes

Abstract: We previously showed that ribosomal protein L13a is required for translational silencing of gamma interferon (IFN-␥)-induced ceruloplasmin (Cp) synthesis in monocytes. This silencing also requires the presence of the GAIT (IFN-gamma activated inhibitor of translation) element in the 3 untranslated region (UTR) of Cp mRNA. Considering that Cp is an inflammatory protein, we hypothesized that this mechanism may have evolved to silence a family of proinflammatory proteins, of which Cp is just one member. To identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 43 publications
4
99
0
Order By: Relevance
“…Another demonstrated function of L13a occurs outside the ribosome. We (11,13) and others (36) have shown that the phosphorylation-dependent release of L13a from 60S subunits in response to extracellular stimuli, such as IFN-␥ treatment, leads to incorporation of L13a into the socalled GAIT complex (11,13,55) and translational silencing of a cohort of mRNAs harboring GAIT elements in their 3=-UTRs (12). Here, we show that the mechanisms of incorporation of L13a protein into the ribosome and into the GAIT complex are distinct.…”
Section: Figmentioning
confidence: 48%
See 2 more Smart Citations
“…Another demonstrated function of L13a occurs outside the ribosome. We (11,13) and others (36) have shown that the phosphorylation-dependent release of L13a from 60S subunits in response to extracellular stimuli, such as IFN-␥ treatment, leads to incorporation of L13a into the socalled GAIT complex (11,13,55) and translational silencing of a cohort of mRNAs harboring GAIT elements in their 3=-UTRs (12). Here, we show that the mechanisms of incorporation of L13a protein into the ribosome and into the GAIT complex are distinct.…”
Section: Figmentioning
confidence: 48%
“…We previously defined an extraribosomal activity of L13a: IFN-␥-induced translational silencing of a cohort of mRNAs encoding inflammatory proteins and containing a GAIT element in their 3=-UTRs (11,12,33,34). This activity requires phosphorylationmediated release of L13a from the 60S ribosomal subunit, which occurs in response to IFN-␥ (13,35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of RPS25 also resulted in inhibition of viral IRES-based translation, though not cap-dependent cellular translation [43]. The interferon-gamma regulated release of RPL13a from the ribosome is also postulated to impact the translation of around 50 genes [44,45]. These findings argue for a very high degree of specificity.…”
mentioning
confidence: 99%
“…This GAIT element is a cis-acting RNA element first identified in the 3 -UTR of the ceruloplasmin (Cp) mRNA in humans. In a more general way, GAIT elements have been found in several immune-related mRNAs showing an important role in gene-specific translation control in innate immunity (Vyas et al, 2009). These elements form a stem-loop structure that is involved in the selective translational silencing of mRNA transcripts.…”
Section: Discussionmentioning
confidence: 99%